A educação nas ações e proposições do Instituto de Organização Racional do Trabalho (1932-1946) - Conceição, Marcelo Rodrigues (2005)
This dissertation presents the results of the inquiry regarding the ideas and projects of the Institute of Rational Organization of the Work, entity created in 1931, for the junction of experts on psychology and entrepreneurs interested in the scientific administration of the work. The research was carried through by means of the analysis of the educational articles, published between 1932-1946, in the Revista do IDORT (and its continuation, Revista de Organização Científica), its main vehicles of communication. Our hypothesis is that the institute, engaged in the modernization and industrialization of the society, considered the education as a decisive factor for the making of the rationalization ideals, thus, for the reorganization of the society. The analysis has been inspired by the hypothesis of Gramsci, that relates fordism , a policy of rationalization applied to the industrial production, to the term Americanism , taken as a deeper process of changes in social and individual life, which conducts the man to his adjustment to the industrial work and to the new standards of consumption then developed with special force and effectiveness in the American society. As the Americanism could be considered as a set of actions that intents the "manufacture" of a new type of man, adjusted to the new requirements of the modern world, so the different modalities of education should be considered as a central point to be investigated. One concludes that IDORT tooks as "education" a series of activities, expressed in terms such as to adjust , to mold , to instruct , to train etc. Supported by sciences such as psychology and biology, and strengthened for the cooperation of educators and entrepreneurs engaged in educative experiences, the education has been considered as the most efficient instrument to manage the rationalization and, therefore, the manufacture of the "new man", considered necessary for the development of the country